An Eksperimental Permeable Asphalt Pavement Using Local Material Domato Stone On Quality Of Porous Asphalt - Firdaus Chairuddin; Wihardi Tjaronge; Muhammad Ramli; Johannes Patanduk (Bandar Lampung University (UBL), 2013)
The lot deposit of Domato Stone as local material from sea location in Banggai island in half Sulawesi of Indonesia. Was still not be exploited better. Some reseaarch in the field of road construction showed that Domato Stone was powefull enough when mixtured asphalt structure. Permeable asphalt pavement or porous friction course is commonly knows as porous asphalt. The porous pavement used in japanes and europe. The pavement consists in a porous overlay allowing rainwater to flow down to the botton the overlay and then to drain on the edges of the pavement. Quality of porous asphalt was developed to drain pavement surface flow through itâs pores, because of is specific propertis to mesure itâs ability to drain the water ( Permeability ), a special measuring device is required. This study is aimed to measure the coefficient of permebility using the constanthead permeability test at transportation laboratory Hasanuddin University. The result were compared with the previous study. The test included horizontal and vertical permeability. There types of gradation were in comporated to : British Graduation, Binamarga Gradation, and Australian Gradation. The tests were carried out at optimum bitumen content, the result shows that the vertical permeability of porous asphalt usig British Gradation were : 0,0914, 0,2841 and 0,2912 Cm/sec. Respectively meanwhile for horizontal permeability were 0,1168, 03212, 0,2897 Cm/Sec. The Marshall stabilities were at in countary to the permeabilities, the porousity were comparable to the permeabilities. The results of research indicates that porous asphalt mixture showed an influence on the value of the characteristics of porous asphalt particularly at concrete waste fraction grading 50% retained 1/2